POLA KEPEKAAN BAKTERI PADA PASIEN KEGANASAN HEMATOLOGI DI RSUP SANGLAH DENPASAR - Rena, Renny A; Suega, Ketut; Bakta, I Made (journal of internal medicine, 2012)
Hematology malignancies patient are particulary susceptible to infection associated with endogen microorganism which origin from body or nosocomial from hospital. The most common etiology of infection is gram-positive oral and gastrointestinal tract. A worsening infection can lead patient to severe septic condition and death. In the last decade, many studies found that species of fungi and virus also has an important etiology of infection in hematology malignancies patient. Empirical antibiotic therapy on the ! rst onset of infection of hematology malignancy are very recomended. It has been proven to decrease morbidity and mortality rate. Empirical antibiotic therapy suitable with the pattern of the microbial in hospital is an important way to overcome the infection on hematology malignancies patient. A total of 36 patient with hematology malignancy who done the blood culture in Sanglah hospital were consecutively recruited and studied in order to study the pro! le of blood culture in hematology malignancy patient. Within six months 36 patients were included, consist of 26 male (72.2%) and 10 female (27.8%). Characteristic of patient are mean of age 42.78 ± 14.25 years. Mean of leukosit 45.76 ± 69.32 x 103/ul, mean of neutrophil dan lymphosit consecutively 27.17 ± 55.80 x 103/ul and 10.29 ± 19.81 x 103/ul. The mean of hemoglobin 8.48 ± 3.26 g/dl, and mean of trombosit 181.21 ± 230.63 x 103/ul. The most common diagnosis found is Acute Myeloblastic Leukemia (AML) 33.3% and Non Hodgkin Lymphoma 22.2%. The result of blood culture mostly no growth (56.3%). The most microbial isolated from the culture is Coagulase Negative Staphilococcus / CONS (11.1%). Antibiotic susceptibility testing for Coagulase Negative Staphilococcus / CONS shows linezolid and chloramphenicol are the most sensitive.
Keywords: blood culture, hematology malignancies, characteristic